Indoor air quality at the Arab governmental girls’ schools [version 2; peer review: 2 approved, 1 approved with reservations] - Abdulmalik Salman Alsaif; Mohammed Tawfiq Aljassim; Sana Abdullah Alsulaiman; Mahmoud Fathy Elsharkawy (F1000Research)
Background A proper and adequate school environment is important for an effective learning process and maintaining the health of the students as they spend most of their time in schools. The physical school environment includes the physical structures; presence of chemicals and biological agents; and the surrounding environment, including air, water, and materials. This study aimed to evaluate the indoor air quality (IAQ) in governmental girls’ schools in the Kingdom of Saudi Arabia (KSA). Methods Seventeen girls’ schools were randomly selected in the Eastern Province of KSA. The indoor levels of PM10 and PM2.5, volatile organic compounds, CO, NO2, and CO2 were measured at different sites inside each school during four months of the year 2020. Results Levels of the six air pollutants were higher inside schools adjacent to roads with moderate traffic activity than schools with low and very low traffic activity. However, the mean level of CO2 inside the selected schools was higher than its outdoor level, suggesting the predominance of an indoor source of CO2. The levels of all measured air pollutants inside governmentally constructed school buildings were higher than those inside the rental type. Conclusion The average levels of air pollutants inside the selected schools were much lower than their air quality guidelines (AQGs), while some CO2 and NO2 levels exceeded their AQGs at some schools.